TEACHERS’ PERCEPTION OF THE APPLICATION OF CONSTRUCTIVIST METHODS IN KOSOVO - B. Çibukçiu; A. Shaqiri (Trakia Journal of Sciences, 2024)
Purpose: The objective of this research study is to explore teachers’ perceptions of the application of constructivist methods during the teaching and learning process in primary school. Methods: In this study, the qualitative research method was used. A semi-structured interview was used as an instrument for data collection. The interviews were conducted with the teachers of grades I to V. The study was conducted in four primary schools of the municipality of Vushtrri, with a total of 20 teachers of gradesI to V. The analysis of qualitative data was done through thematic analysis. Results: The analysis identified several key themes, including the perceived benefits of constructivist methods in increasing student engagement and understanding, the challengesof implementing these methods in the classroom, and the need for ongoing professional support and adequate resources. Educators emphasize the need to create conditions for the use of constructivist methods by education policy makers. Furthermore, the research has contributed to increasing the awareness of teachers for the application of constructivist methods regardless of the challenges they encounter during their application. Conclusion: Based on the findings, this study proposes a constructivist approach, challenging teachers who focus on the traditional approach.